Genome instability due to ribonucleotide incorporation into DNA - Nick McElhinny, Stephanie A. (2010)
Maintaining the chemical identity of DNA depends on ribonucleotide exclusion by DNA polymerases. However, ribonucleotide exclusion during DNA synthesis in vitro is imperfect. To determine if ribonucleotides are incorporated during DNA replication in vivo, we substituted leucine or glycine for an active site methionine in yeast DNA polymerase ε (Pol ε). Compared to wild type Pol ε, ribonucleotide incorporation in vitro was 3-fold lower for M644L and 11-fold higher for M644G Pol ε. This hierarchy was re-capitulated in vivo in yeast strains lacking RNase H2. Moreover, the pol2-M644G rnh201Δ strain progressed more slowly through S-phase, had elevated dNTP pools and generated 2–5 base pair deletions in repetitive sequences at a high rate and gene orientation-dependent manner. The data indicate that ribonucleotides are incorporated during replication in vivo, that they are removed by RNase H2-dependent repair, and that defective repair results in replicative stress and genome instability via DNA strand misalignment.